2011
DOI: 10.1089/jayao.2011.0033
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life of Young Adult Survivors of Childhood Cancer: A Review of Qualitative Studies

Abstract: Purpose: The occurrence of late effects, combined with traditional growth and developmental issues, can significantly affect the health-related quality of life (HRQOL) of young adult survivors of childhood cancer (YASCC). Limited HRQOL measurement tools have been developed or validated for YASCC. The purpose of this study was to identify the domains of HRQOL that are unique to YASCC by conducting a systematic review of qualitative studies. Specifically, we compared the findings to the classical framework of HR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 44 publications
1
45
0
1
Order By: Relevance
“…Changes in appearance, ability to participate in regular school activities and athletics, increased family stress, and heightened uncertainty over future educational and work endeavors were the most immediate concerns. However, consistent with prior studies [10,28], AYA with cancer in this sample also noted resiliencies. AYA survivors experience growth through cancer diagnosis and treatment and have a more positive outlook toward the future with a stronger sense of identity and confidence in overcoming adversity.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Changes in appearance, ability to participate in regular school activities and athletics, increased family stress, and heightened uncertainty over future educational and work endeavors were the most immediate concerns. However, consistent with prior studies [10,28], AYA with cancer in this sample also noted resiliencies. AYA survivors experience growth through cancer diagnosis and treatment and have a more positive outlook toward the future with a stronger sense of identity and confidence in overcoming adversity.…”
Section: Discussionsupporting
confidence: 90%
“…Of note, there were few differences in responses across AYA subgroups based on age at time of survey completion, age at time of diagnosis, and whether AYA were on or off treatment at the time of survey completion indicating that there is consistency in the needs of AYA across this developmental period and the cancer treatment continuum. Based on the qualitative data, limitations to HRQL associated with cancer and treatment challenges paralleled domains noted by Nightingale and colleagues [10]. These included concerns about body image, family life, friendships and romance, and school.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…According to Patenaude and Kupst [9], low or average levels of distress are found in survivors of paediatric cancer; however there are also subsets of more vulnerable patients. A literature review on qualitative studies identified seven important areas of wellbeing: physical, social, psychological, spiritual and fertility/sexual wellbeing, resilience and body appearance [10].…”
Section: Introductionmentioning
confidence: 99%
“…Given that the survival rate is greater than 80%, pediatric cancer patients are facing many life challenging issues. For example, one recent article discusses the potential missing content of PROs critical to childhood cancer survivors by reviewing the published “qualitative” studies and comparing the results to the conventional PRO framework with physical, psychological and social domains [13]. This study found that childhood survivors are behind in several developmental milestones, and survivors have unique concerns related to cancer such as normalcy, independency, fertility, self-identity, and body image.…”
mentioning
confidence: 99%